Penerapan Layanan Bimbingan Klasikal Berbasis Tri Hita Karana Dalam Meningkatkan Karakter Siswa Kelas VII B SMP Negeri 1 Mengwi Tahun Pelajaran 2023/2024 - I Wayan Nova Saputra; I Made Mahaardhika (Universitas 45 Surabaya, 2024)
This research aims to instill positive attitudes, traits and characteristics from the application of tri hita karana in the form of classical guidance services based on tri hita karana which was tested on class VII B students of SMP Negeri 1 Mengwi for the 2023/2024 academic year. This research is a type of action research which covers several aspects, namely planning, implementation, observation/evaluation and reflection stages and uses 2 cycles. The hypothesis proposed in this research is that by using classical guidance services based on Tri Hita Karana, it can improve the character of class VII B students at SMP Negeri 1 Mengwi for the 2023/2024 academic year. The research subjects in the tri hita karana-based classical guidance service were all students in class VII B of SMP Negeri 1 Mengwi for the 2023/2024 academic year. Based on the results of this research, it was concluded that the application of classical guidance services based on tri hita karana could improve student character where there were significant changes, there was an average increase of 27% in cycle I, while in cycle II the average increase was 57.6%, so the application of guidance services Classical based on Tri Hita Karana is considered effective for improving students' character problems in the modern era.